2020
DOI: 10.1177/0308518x20958724
|View full text |Cite
|
Sign up to set email alerts
|

Regression to the tail: Why the Olympics blow up

Abstract: The Olympic Games are the largest, highest-profile, and most expensive megaevent hosted by cities and nations. Average sports-related costs of hosting are $12.0 billion. Non-sports-related costs are typically several times that. Every Olympics since 1960 has run over budget, at an average of 172 percent in real terms, the highest overrun on record for any type of megaproject. The paper tests theoretical statistical distributions against empirical data for the costs of the Games, in order to explain the cost ri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 55 publications
0
51
0
2
Order By: Relevance
“…Not only because of that but also because of the expensive construction of the Olympic stadium, this edition had the largest ever cost overrun in Olympic financial history (720%). 37 Perhaps recognising the consequences of the decision, in 1979 the IOC changed the Olympic Charter allowing, for the first time, a host city to 'share its privilege with other cities or sites in the same country upon agreement of the IOC' but, if so, additional accommodation should be provided for the participants at those cities -'satellite' Olympic villages. 38 Consequently, more local communities, authorities and entities needed to be involved in order to provide the required services.…”
Section: The Fireback Of Olympic Politicsmentioning
confidence: 99%
“…Not only because of that but also because of the expensive construction of the Olympic stadium, this edition had the largest ever cost overrun in Olympic financial history (720%). 37 Perhaps recognising the consequences of the decision, in 1979 the IOC changed the Olympic Charter allowing, for the first time, a host city to 'share its privilege with other cities or sites in the same country upon agreement of the IOC' but, if so, additional accommodation should be provided for the participants at those cities -'satellite' Olympic villages. 38 Consequently, more local communities, authorities and entities needed to be involved in order to provide the required services.…”
Section: The Fireback Of Olympic Politicsmentioning
confidence: 99%
“…For example, Khan et al found in a 2017 survey of more than fifty high‐profile development projects (primarily regarding infrastructure construction) that social media pressures from “adverse stakeholders” exerted powerful influence over the scope, timing, and terms of these initiatives, all of which are normally the subjects of multiparty negotiations (Khan et al 2017). In Boston, local residents organized via social media helped overturn the city’s successful bid to host the 2024 Olympics, despite widespread support among the city’s leadership class (Sims 2017)—a potentially beneficial outcome for the city given the long history of cost overruns and poor return on investment from hosting the Games (Flyvbjerg et al 2020).…”
Section: Insights From Case Studies Exploring Social Media In Negotiamentioning
confidence: 99%
“…Den tredje betingelsen for innovativ eventledelse er at eventet integreres i stedets eller byens langsiktige utviklingsmål. Svaert ofte har store idrettsarrangementer pådratt seg store økonomiske ringvirkninger i ettertid som arrangørene enten ikke ville, eller kunne se for seg (Flyvbjerg, Budzier & Lunn, 2020;Olderøien & Solberg, 2019). Før løpet hadde Zürich oppnådd førsteplass på Arcadis Sustainable Cities Index 2016 og andreplass på Mercer Quality of Living Ranking 2018, 5 og kunne derfor se Formel E-løpet som en naturlig forlengelse av dette arbeidet -gitt at arrangørene av det godtok byens betingelser for støtte.…”
Section: Konklusjon: Tre Betingelser For Innovative Eventledelseunclassified